Evaluasi Kebergunaan Aplikasi Pemesanan Makanan Cepat Saji dengan System Usability Scale - Fadlan, Muhammad; Julius (Jurnal INSYPRO (Information System and Processing), 2023)
Fast food ordering apps have become an important element in the digital transformation of the food industry. The success of a food ordering application is not only determined by its functionality and features, but also by its level of usability. Usability evaluation is a key aspect in understanding the extent to which an application meets user needs and expectations. In order to increase user satisfaction with application use, this research aims to test the usability of a fast food ordering application using the System Usability Scale (SUS) approach. One of the important elements in this research is filling out a questionnaire carried out by respondents regarding the level of usefulness of the food ordering application. The research results show that the level of usefulness is at a SUS score of 83.08 which is included in the "Excellent" category in terms of Adjective Rating.